Protective and Suppressing Electromagnetic Interference Properties of Epoxy Coatings Containing Nano-Sized NiZn Ferrites - Miszczyk, Andrzej (Frontiers in Materials, 2020)
Nano-crystalline ferrites with the chemical formula NixZn(1-x)Fe2O4, where x=0, 0.2, 0.4, 0.6, 0.8, 1.0, were synthesized using a co-precipitation method. The obtained ferrites were investigated by X-ray diffraction (XRD). The corrosion inhibiting behavior of nano-sized ferrites was tested using carbon steel samples and 10% aqueous ferrite extracts. Results were compared with previous data obtained for micro-sized ceramic ferrites. Nanoparticles show more favourable properties regarding inhibiting corrosion processes on steel. 2mm thick epoxy coatings on steel containing 10% vol. of nano-sized ferrites has been investigated as a microwave absorber. The microwave reflectivity of the coating was measured within the range from 6.5 to 15 GHz. Both the nano- and micro-sized ferrites included in the coatings exhibited different reflection loss spectra. The greatest attenuation on a level of 8-16 dB was observed. The nano-ferrite-filled epoxy coating exhibited a higher minimum reflection frequency in comparison with the micro-ferrite-filled coating. A frequency shift of 1-2 GHz was observed.